Agroclimatic potential of sunflower in Paraiba State, Brazil. II. Water requeriments - Zaffaroni, Eduardo; Silva, Marcos A. V.; de Azevedo, Pedro V. (Pesquisa Agropecuaria Brasileira, 1994)
Water requirements of sunflower (Helianthus annuus L.) were compared with climatical conditions in order to determine better planting dates in different homogenous micro-regions (HMR) in Paraíba, Brazil. In the agroclimatic analysis of water requirements for sunflower, the total water requirement TWR (product of monthly evapotranspiration and relative water use during the crop growing season) and the expected potential water deficit (PWD) were calculated. Regarding water availability, months with minimum PWD were considered as suitable planting dates. It was concluded, for dryland conditions, that the most suitable planting time of sunflower on Paraíba State would be through the period from March to April for HMR having long rainy season, and February to March for HMR having short rainy season. There are some HMR where sunflower production would be not appropriated.